La «Relació verdadera» de Maximilià Cerdà de Tallada - Lozano, Josep (Caplletra. Revista Internacional de Filologia, 2001)
This study and critical edition of a text by Cerdà de Tallada, which has never been published so far, deals with the expulsion of the Valencian Moors in 1609. The text, which is incomplete, contains, nevertheless, numerous facts of historiographic interest and is a remarkable example of Valencian chronicles from the Baroque period.